HUBUNGAN ASUPAN VITAMIN D DENGAN MEAN ARTERIAL PRESSURE (MAP) DAN PERINATAL OUTCOME PADA PREEKLAMSIA BERAT - Fitriani, Indah; Yusrawati; Effendi, Rinal (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Preeclampsia as a multifactorial disease is associated with vitamin D deficiency. Vitamin D is known to have a potential effect on regulation of the immune system and blood pressure. Consequently, vitamin D deficiency have been linked to poor perinatal outcomes and mean arterial pressure (MAP). This study aims to determine the relationship between vitamin D intake and perinatal outcomes such as preterm pregnancy, birth weight, APGAR scores, and mean arterial pressure (MAP). Design of this study was observational analytic with cross-sectional approach. This study was conducted in the obstetrics and gynecology ward and the medical record department of RSUP Dr. M. Djamil Padang in May 2022 – December 2022. Total sample of this study was 60 pregnancy women with severe preeclampsia. This study found that 75% of mothers aged 20-35 years, 51.7% of high school education, 55% of BMI ≥ 30 kg/m2, 35% of multiparas, 58.3% intake of vitamin D <15 mcg. Statistical test results showed a significant relationship between vitamin D intake and birth weight [p=0.002;OR=8.396(2.279-30.924)], gestational age [p=0.010;OR=6.089 (1.648-22.497)], APGAR score minute 1 [p=0.035;OR=3.677 (1.230-10.986)], APGAR score minute 5 [p=0.035;OR=8.308(0.978-70.553)] and there was no relationship between vitamin D intake and mean arterial pressure (MAP). To conclude, vitamin D intake has a significant relationship with birth weight, gestational age, APGAR score and has no significant relationship with MAP